2012
DOI: 10.1111/j.1439-0507.2012.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizophyllum commune as an emerging fungal pathogen: a review and report of two cases

Abstract: We report Schizophyllum commune as the aetiological agent of one case each of allergic broncho-pulmonary mycosis (ABPM) and pulmonary fungal ball, and present a literature review. The fungus was characterised by clamp connections, hyphal spicules, and formation of basidiocarps with basidiospores. The phenotypic identification was confirmed by sequencing of the ITS region. To-date, ABPM and pulmonary fungal ball to S. commune have been reported exclusively from Japan and North America respectively. Of the 71 gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
121
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 53 publications
3
121
0
2
Order By: Relevance
“…It is known that basidiomycetous molds chronically colonizing the lung can precipitate invasive disease and/or sensitize individuals to fungal antigens, leading to allergic fungal cough, allergic sinusitis, asthma, and ABPM (13,(26)(27)(28)(29). In the present study, these molds were most frequently identified as asymptomatic colonizers in patients with respiratory ailments.…”
Section: Discussionmentioning
confidence: 53%
“…It is known that basidiomycetous molds chronically colonizing the lung can precipitate invasive disease and/or sensitize individuals to fungal antigens, leading to allergic fungal cough, allergic sinusitis, asthma, and ABPM (13,(26)(27)(28)(29). In the present study, these molds were most frequently identified as asymptomatic colonizers in patients with respiratory ailments.…”
Section: Discussionmentioning
confidence: 53%
“…In routine laboratories, the induction of sporulation usually requires about 3 weeks and is associated with high failure rates (34). Therefore, molecular methods, such as DNA sequence analysis, are required for accurate identification of this kind of fungus that fails to sporulate (13). The most commonly sequenced markers in Schizophyllum are the ITS and D1/D2 regions of the LSU (13,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, molecular methods, such as DNA sequence analysis, are required for accurate identification of this kind of fungus that fails to sporulate (13). The most commonly sequenced markers in Schizophyllum are the ITS and D1/D2 regions of the LSU (13,33,34). However, Schizophyllum has a highly conserved ITS region, which is often difficult to amplify and to sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations